The role of glucosinolates and the jasmonic acid pathway in resistance of Arabidopsis thaliana against molluscan herbivores. Issue 5 (22nd January 2014) - Falk, Kimberly L.; Kästner, Julia; Bodenhausen, Natacha; Schramm, Katharina; Paetz, Christian; Vassão, Daniel G.; Reichelt, Michael; von, Dietrich; Bergelson, Joy; Erb, Matthias; Gershenzon, Jonathan; Meldau, Stefan
Abstract Although slugs and snails play important roles in terrestrial ecosystems and cause considerable damage on a variety of crop plants, knowledge about the mechanisms of plant immunity to molluscs is limited. We found slugs to be natural herbivores of Arabidopsis thaliana and therefore investigated possible resistance mechanisms of this species against several molluscan herbivores. Treating wounded leaves with the mucus residue ('slime trail') of the Spanish slug Arion lusitanicus increased wound‐induced jasmonate levels, suggesting the presence of defence elicitors in the mucus. Plants deficient in jasmonate biosynthesis and signalling suffered more damage by molluscan herbivores in the laboratory and in the field, demonstrating that JA‐mediated defences protect A. thaliana against slugs and snails. Furthermore, experiments using A. thaliana mutants with altered levels of specific glucosinolate classes revealed the importance of aliphatic glucosinolates in defending leaves and reproductive structures against molluscs. The presence in mollusc faeces of known and novel metabolites arising from glutathione conjugation with glucosinolate hydrolysis products suggests that molluscan herbivores actively detoxify glucosinolates. Higher levels of aliphatic glucosinolates were found in plants during the night compared to the day, which correlated well with the nocturnal activity rhythms of slugs and snails. Our data highlight the function of well‐known antiherbivore defence pathways in resistance against slugs and snails and suggest an important role for the diurnal regulation of defence metabolites against nocturnal molluscan herbivores.